2005
DOI: 10.1086/429556
|View full text |Cite
|
Sign up to set email alerts
|

The Velocity Field of Baryonic Gas in the Universe

Abstract: The dynamic evolution of the baryonic intergalactic medium ( IGM) caused by the underlying dark matter gravity is governed by the Navier-Stokes equations in which many cooling and heating processes are involved. However, it has long been recognized that the growth mode dynamics of cosmic matter clustering can be sketched by a random force driven Burgers equation if cooling and heating are ignored. Just how well the dynamics of the IGM can be described as a Burgers fluid has not been fully investigated, probabl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 54 publications
2
23
0
Order By: Relevance
“…The H i and He ii Ly absorption lines of QSO HE 2347 cannot be explained by thermal broadening, but are consistent with turbulence broadening ( Zheng et al 2004;Liu et al 2006). Moreover, samples produced by cosmological hydrodynamic simulations also reveal the statistical decoupling of baryon matter from dark matter and the non-Gaussian features of Bergers' turbulence (He et al 2004Kim et al 2005).…”
Section: Introductionsupporting
confidence: 58%
“…The H i and He ii Ly absorption lines of QSO HE 2347 cannot be explained by thermal broadening, but are consistent with turbulence broadening ( Zheng et al 2004;Liu et al 2006). Moreover, samples produced by cosmological hydrodynamic simulations also reveal the statistical decoupling of baryon matter from dark matter and the non-Gaussian features of Bergers' turbulence (He et al 2004Kim et al 2005).…”
Section: Introductionsupporting
confidence: 58%
“…It has been shown recently that in the nonlinear regime the velocity field v(x) of cosmic baryon matter consists of strong shocks on various spatial scales and in high and low mass density area ( Kim et al 2005). The statistical behavior of the velocity field is similar to a fully developed turbulence (He et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the field of the transmitted flux fluctuations is highly intermittent. This shows again that the cuspy feature of cosmic clustering can be seen in high mass density areas, like massive halos, as well as in low mass density areas, like the clouds of Ly absorption clouds (Pando et al 2004;He et al 2004He et al , 2005Kim et al 2005). Actually, the success of the semianalytical lognormal model (Bi & Davidsen 1997) in explaining the Ly forest has already indicated that the mass field of the cosmic baryon gas is probably intermittent, because a lognormal field is intermittent.…”
Section: Structure Functionsmentioning
confidence: 82%
“…If the index is constant, the intermittency exponent should be scale-independent. Therefore, the scale dependence of the intermittency exponent indicates that the distribution of baryon gas is decoupled from the underlying dark matter (e.g., He et al 2004;Kim et al 2005). The data of HE 2347À4342 only are unable to test the prediction of scale dependence of the intermittency exponent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation